Preparation method of composite ceramic nanofiltration membrane
By combining the ceramic membrane support with the modified microporous polymer, a composite ceramic nanofiltration membrane was prepared, which solved the problem of limited application of the nanofiltration membrane in high temperature, strong acid and strong alkali or high pressure environments, and achieved efficient separation performance and structural stability.
Patent Information
- Application Number
- CN202411769344.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, nanofiltration membranes are limited in applications in high temperature, strong acid and alkali or high pressure environments, and the membrane flux and molecular weight of the retention are likely to change after long-term use, resulting in a degradation of performance.
Using the preparation method of composite ceramic nanofiltration membrane, a composite membrane support with modified microporous polymers (PIMs) was combined with ultrasonic treatment and silane coupling agent for activation and functionalization, forming a composite membrane with high permeability flux and stable structure.
A composite ceramic nanofiltration membrane that maintains efficient separation performance under high temperature, strong acid and alkali or high pressure environments has high permeability flux, excellent separation performance and good structural stability, avoiding the reduction of performance after long-term use.
Smart Images

Figure SMS_1 
Figure FDA0005169845520000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane separation, and specifically relates to a method for preparing a composite ceramic nanofiltration membrane. Background Art
[0002] Membrane separation technology is a technology that uses a selectively permeable membrane to separate, grade, purify or enrich multi-component gases or liquids under the drive of pressure difference or osmotic pressure. Due to its advantages of high selective permeability, low operating cost, pollution-free and continuous operation, membrane separation technology has been widely studied and applied in wastewater treatment, oil-water separation, seawater distillation, drinking water disinfection, etc. Nanofiltration (NF) is a membrane separation technology between ultrafiltration (UF) and reverse osmosis (RO), with an average pore size between 1-2nm and a molecular weight cutoff of 200-1000Da.
[0003] Typical organic membranes are often made of cellulose esters, polysulfones, polyamides, polyesters and olefins. They are widely used due to their low price and rich variety. However, due to the properties of organic membranes themselves, their application in many fields is severely restricted, such as application in high temperature, strong acid and alkali and high pressure environments. Compared with organic membranes, inorganic membranes have attracted more and more attention from scholars due to their high mechanical strength, good chemical stability and high temperature resistance, and have been widely used in many fields. Summary of the invention
[0004] In view of the above-mentioned problems existing in the prior art, the purpose of the present invention is to design a technical solution for a method for preparing a composite ceramic nanofiltration membrane. The preparation process is simple and the production cost is low. The composite membrane is made by combining inorganic materials with organic high molecular polymers, and has the advantages of both organic membranes and inorganic membranes. It has high permeation flux, high separation performance and good structural stability.
[0005] The method for preparing a composite ceramic nanofiltration membrane is characterized by comprising the following steps:
[0006] 1) Treatment of the ceramic support: After ultrasonic treatment, the ceramic membrane support is immersed in a strong alkaline aqueous solution for activation treatment, and then placed in an oven for drying to obtain an activated ceramic membrane support; after cooling, it is immersed in an ethanol solution of a silane coupling agent, and then washed with ethanol or water, and placed in an oven for drying to obtain a grafted ceramic membrane support;
[0007] 2) Functionalization of PIMs: introducing hydroxyl, amino or carboxyl active groups into the PIM chain structure through functionalization reaction;
[0008] 3) Soaking the ceramic support treated in step 1) in the chloroform solution of the functionalized PIMs in step 2), taking it out after soaking, drying it in the shade, and putting it in an oven for heat treatment, so that the functional groups on the functionalized PIMs are connected to the silane coupling agent of the ceramic membrane support, thereby obtaining a composite ceramic nanofiltration membrane.
[0009] The method for preparing a composite ceramic nanofiltration membrane is characterized in that in step 1): the material of the ceramic membrane support is aluminum oxide, titanium oxide or zirconium oxide, and is in sheet, tubular or hollow fiber form, with a pore size of 10-50 nm; the strong base is at least one of sodium hydroxide, potassium hydroxide, and lithium hydroxide, and the concentration of the strong base aqueous solution is 0.1-1.0 mol / L, preferably 0.2-0.8 mol / L, and more preferably 0.4-0.5 mol / L.
[0010] The method for preparing a composite ceramic nanofiltration membrane is characterized in that in step 1): the ultrasonic time is 0.5-6h, preferably 1-5h, more preferably 2-3h; the oven drying temperature in the activation treatment is 110-180°C, and the time is 6-12h; preferably the drying temperature is 140-160°C, and the time is 8-10h.
[0011] The method for preparing a composite ceramic nanofiltration membrane is characterized in that in step 1): the silane coupling agent is at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-diethylaminomethyltriethoxysilane, and γ-diethylenetriaminopropyltrimethoxysilane; the concentration of the silane coupling agent in the ethanol solution is 1-20mmol / L, preferably 5-15mmol / L, and more preferably 8-12mmol / L; the oven drying temperature in the grafting treatment is 110-180°C and the time is 6-12h; the preferred drying temperature is 150-160°C and the time is 9-10h.
[0012] The method for preparing a composite ceramic nanofiltration membrane is characterized in that in step 2), the PIMs is one of PIM-1-6, and the synthesis route of PIM-1-6 and the required monomer molecular structure are as follows:
[0013]
[0014] The method for preparing a composite ceramic nanofiltration membrane is characterized in that in step 2): the functionalization of PIMs is the introduction of at least one of hydroxyl, amino, and carboxyl groups; the mass fraction of the chloroform solution of the functionalized PIMs is 1wt%-5wt%, preferably 2wt%-3wt%.
[0015] The method for preparing a composite ceramic nanofiltration membrane is characterized in that in step 3): the oven drying temperature is 40-80°C and the time is 6-12h; preferably the drying temperature is 50-60°C and the time is 8-10h.
[0016] The preparation method of a composite ceramic nanofiltration membrane is characterized in that the PIM-1-6 synthesis method includes the PIM-1 synthesis, and the specific steps are: putting 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindole (A1) and tetrafluoroterephthalonitrile (B1) in an equal molar ratio into a three-necked flask containing N,N-dimethylformamide (DMF), adding a small amount of potassium carbonate (K2CO3), and reacting at 115-125°C under vacuum conditions for 1-4 hours. After the reaction is completed, washing with deionized water and methanol in turn, filtering and drying in a vacuum oven at 105-115°C for 22-26 hours to obtain PIM-1;
[0017] The synthesis method of PIM-2-6 is the same as that of PIM-1, except that the reactants are replaced with A1 and decafluorobiphenyl (B2), A1 and B3, A2 and B1, A2 and B2, and 1,2,4,5-tetrahydroxybenzene (A3) and B2.
[0018] In the present invention, the pore size, PIMs, silane coupling agent, type and concentration of functionalized modified substances of the ceramic ultrafiltration membrane all have a direct impact on the performance of the nanofiltration membrane.
[0019] The above-mentioned method for preparing a composite ceramic nanofiltration membrane uses a ceramic membrane with a fixed pore structure as a support and loads modified self-microporous polymers (PIMs) in its pores, which can effectively prevent the pore structure changes caused by segment relaxation of PIMs due to long-term use, and avoid large changes in membrane flux and retention molecular weight under long-term use; the prepared composite membrane has the advantages of both organic membranes and inorganic membranes, and has high permeation flux, high separation performance and good structural stability. DETAILED DESCRIPTION
[0020] The present invention is described clearly and completely below in conjunction with specific embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Example 1
[0022] 1) Treatment of the support: The ceramic membrane was placed in deionized water for 1 hour of ultrasonic treatment, and a sheet-type alumina ceramic membrane was selected as the support, which had a thickness of 2 mm, an outer diameter of 22 mm, and a pore size of 10 nm; then, it was immersed in a 1 mol / L sodium hydroxide solution for 2 hours, taken out and dried naturally, and then dried in a 110°C oven for 6 hours; after cooling, it was immersed in a 2 mmol γ-aminopropyltrimethoxysilane ethanol solution, reacted at room temperature for 12 hours, and then rinsed with deionized water several times, and dried in a 110°C oven for 6 hours;
[0023] 2) Synthesis of PIM-1: 1 mmol 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindole and 1 mmol tetrafluoroterephthalonitrile were added to a three-necked round-bottom flask containing 20 ml N,N-dimethylformamide, and 2 mmol potassium carbonate was added. The mixture was reacted at 120° C. for 2 hours under a nitrogen atmosphere. After the reaction, the mixture was washed with deionized water and methanol in sequence, filtered, and dried in a vacuum oven at 110° C. for 24 hours to obtain PIM-1;
[0024] 3) PIM-1 functionalization: PIM-1 was functionalized with ethanolamine. PIM-1 powder was placed in a three-necked flask, and an appropriate amount of ethanolamine was added. The mixture was reacted at 105° C. for 12 hours under a nitrogen atmosphere. After the reaction, the mixture was poured into ethanol and stirred for 15 minutes. The precipitate was filtered out, washed with deionized water, and dried in a vacuum oven at 110° C. for 24 hours to obtain -OH-modified PIM-1 (PIM-1-OH).
[0025] 4) Preparation of composite ceramic nanofiltration membrane: The -OH-modified PIM-1 was dissolved in chloroform at a concentration of 5 wt %. The pretreated support was immersed in the solution for 10 minutes, taken out and dried in the shade, and then placed in an oven at 80°C for heat treatment for 12 hours to complete the preparation of the composite ceramic nanofiltration membrane.
[0026] Membrane separation performance test: Under the test conditions of room temperature and 0.5 MPa pressure, the flux of the composite ceramic nanofiltration membrane for pure water is 32.3 LHM, and the retention rate for 0.2 wt% methyl orange (molecular weight 327 Da) aqueous solution is 95.3%.
[0027] Solvent resistance test: The composite ceramic nanofiltration membrane was immersed in acetone for 168 hours at 40°C. Then, the pure water flux was tested at room temperature and 0.5 MPa pressure to be 34.1 LHM, and the rejection rate for 0.2 wt% methyl orange (molecular weight 327 Da) aqueous solution was 93.2%.
[0028] Embodiment 2:
[0029] 1) The treatment of the support is the same as in Example 1: the ceramic membrane is placed in deionized water for 1 hour of ultrasonic treatment, and a sheet-type alumina ceramic membrane is selected as the support. The support has a thickness of 2 mm, an outer diameter of 22 mm, and a pore size of 50 nm. The support is then immersed in a 1 mol / L sodium hydroxide solution for 2 hours, taken out and dried naturally, and then placed in a 110° C. oven for 6 hours. After cooling, it is immersed in a 2 mmol γ-aminopropyltrimethoxysilane ethanol solution, reacted at room temperature for 12 hours, and then rinsed with deionized water several times and dried in a 110° C. oven for 6 hours;
[0030] 2) Synthesis of PIM-1 was the same as in Example 1: 1 mmol of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindole and 1 mmol of tetrafluoroterephthalonitrile were added to a three-necked round-bottom flask containing 20 ml of N,N-dimethylformamide, and 2 mmol of potassium carbonate were added, and the mixture was reacted at 120°C for 2 hours under a nitrogen atmosphere. After the reaction, the mixture was washed with deionized water and methanol in sequence, filtered, and dried in a vacuum oven at 110°C for 24 hours to obtain PIM-1;
[0031] 3) PIM-1 functionalization was the same as in Example 1: PIM-1 was functionalized with ethanolamine. PIM-1 powder was placed in a three-necked flask, and an appropriate amount of ethanolamine was added. The mixture was reacted at 105° C. for 12 hours under a nitrogen atmosphere. After the reaction, the mixture was poured into ethanol and stirred for 15 minutes. The precipitate was filtered out, washed with deionized water, and dried in a vacuum oven at 110° C. for 24 hours to obtain -OH-modified PIM-1 (PIM-1-OH).
[0032] 4) Preparation of composite ceramic nanofiltration membrane: The -OH-modified PIM-1 was dissolved in chloroform at a concentration of 1 wt %, and the pretreated support was immersed in the solution for 10 minutes, taken out and dried in the shade, and then placed in an oven at 80°C for heat treatment for 12 hours to complete the preparation of the composite ceramic nanofiltration membrane.
[0033] Membrane separation performance test: Under the test conditions of room temperature and 0.5 MPa pressure, the flux of the composite ceramic nanofiltration membrane for pure water is 54.1 LHM, and the retention rate for 0.2 wt% Acid Red 94 (molecular weight 1050 Da) aqueous solution is 93.2%.
[0034] Solvent resistance test: The composite ceramic nanofiltration membrane was immersed in acetone at 40°C for 168 hours. Then, the pure water flux was tested at room temperature and 0.5 MPa pressure to be 56.3 HM, and the rejection rate of 0.2 wt% Acid Red 94 (molecular weight 1050 Da) aqueous solution was 91.4%.
[0035] Embodiment 3:
[0036] 1) The treatment of the support is the same as in Example 1: the ceramic membrane is placed in deionized water for 1 hour of ultrasonic treatment, and a sheet-type alumina ceramic membrane is selected as the support. The support has a thickness of 2 mm, an outer diameter of 22 mm, and a pore size of 10 nm; then it is immersed in a 1 mol / L sodium hydroxide solution for 2 hours, taken out and dried naturally, and then placed in a 110°C oven for 6 hours. After cooling, it is immersed in a 2 mmol γ-aminopropyltrimethoxysilane ethanol solution, reacted at room temperature for 12 hours, and then rinsed with deionized water several times and dried in a 110°C oven for 6 hours.
[0037] 2) Synthesis of PIM-2: 1mmol 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindole and 1mmol decafluorobiphenyl were added to a three-necked round-bottom flask containing 20ml N,N-dimethylformamide, and 2mmol potassium carbonate was added. The mixture was reacted at 120°C for 2 hours under a nitrogen atmosphere. After the reaction, the mixture was washed with deionized water and methanol in turn, filtered, and dried in a vacuum oven at 110°C for 24 hours to obtain PIM-2.
[0038] 3) PIM-2 functionalization: PIM-2 was functionalized with ethanolamine. PIM-2 powder was placed in a three-necked flask, and an appropriate amount of ethanolamine was added. The mixture was reacted at 105°C for 12 hours under a nitrogen atmosphere. After the reaction, the mixture was poured into ethanol. After stirring for 15 minutes, the precipitate was filtered out, washed with deionized water, and dried in a vacuum oven at 110°C for 24 hours to obtain -OH-modified PIM-2 (PIM-2-OH).
[0039] 4) Preparation of composite ceramic nanofiltration membrane: The -OH-modified PIM-2 was dissolved in chloroform at a concentration of 5 wt%, and the pretreated support was immersed in the solution for 10 minutes, taken out and dried in the shade, and then placed in an oven at 80°C for heat treatment for 12 hours. The preparation of the composite ceramic nanofiltration membrane was completed.
[0040] Membrane separation performance test: Under the test conditions of room temperature and 0.5 MPa pressure, the flux of the composite ceramic nanofiltration membrane for pure water is 30.2 LHM, and the retention rate for 0.2 wt% methyl red (molecular weight 269.3 Da) aqueous solution is 97.3%.
[0041] Solvent resistance test: The composite ceramic nanofiltration membrane was immersed in acetone at 40°C for 168 hours. Then, the pure water flux was tested at room temperature and 0.5 MPa pressure to be 32.3 LHM, and the retention rate of 0.2 wt% methyl red (molecular weight 269.3 Da) aqueous solution was 94.5%.
[0042] Embodiment 4:
[0043] 1) The treatment of the support is the same as in Example 1: the ceramic membrane is placed in deionized water for 1 hour of ultrasonic treatment, and a sheet-type alumina ceramic membrane is selected as the support, which has a thickness of 2 mm, an outer diameter of 22 mm, and a pore size of 50 nm; then immersed in a 1 mol / L sodium hydroxide solution for 2 hours, taken out and naturally dried, and then placed in a 110°C oven for 6 hours. After cooling, it is immersed in a 2 mmol γ-aminopropyltrimethoxysilane ethanol solution, reacted at room temperature for 12 hours, and then rinsed with deionized water several times and dried in a 110°C oven for 6 hours.
[0044] 2) Synthesis of PIM-2 was the same as in Example 3: 1 mmol 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindole and 1 mmol decafluorobiphenyl were added to a three-necked round-bottom flask containing 20 ml N,N-dimethylformamide, and 2 mmol potassium carbonate was added. The mixture was reacted at 120°C for 2 hours under a nitrogen atmosphere. After the reaction, the mixture was washed with deionized water and methanol in turn, filtered, and dried in a vacuum oven at 110°C for 24 hours to obtain PIM-2.
[0045] 3) PIM-2 functionalization is the same as in Example 3: PIM-2 is functionalized with ethanolamine. PIM-2 powder is placed in a three-necked flask, and an appropriate amount of ethanolamine is added. The mixture is reacted at 105°C for 12 hours under a nitrogen atmosphere. After the reaction, it is poured into ethanol. After stirring for 15 minutes, the precipitate is filtered out, washed with deionized water, and dried in a vacuum oven at 110°C for 24 hours. -OH-modified PIM-2 (PIM-2-OH) is obtained.
[0046] 4) Preparation of composite ceramic nanofiltration membrane is the same as in Example 2: the above-mentioned -OH-modified PIM-1 is dissolved in chloroform at a concentration of 1 wt%. The pretreated support is immersed in the solution for 10 minutes, taken out and dried in the shade, and heat-treated in an oven at 80°C for 12 hours. The preparation of the composite ceramic nanofiltration membrane is completed.
[0047] Membrane separation performance test: Under the test conditions of room temperature and 0.5 MPa pressure, the flux of the composite ceramic nanofiltration membrane for pure water is 52.3 LHM, and the retention rate for 0.2 wt% Acid Red 94 (molecular weight 1050 Da) aqueous solution is 94.3%.
[0048] Solvent resistance test: The composite ceramic nanofiltration membrane was immersed in acetone at 40°C for 168 hours. Then, the pure water flux was tested at room temperature and 0.5 MPa pressure to be 54.8 HM, and the rejection rate of 0.2 wt% Acid Red 94 (molecular weight 1050 Da) aqueous solution was 92.4%.
[0049] Embodiment 5:
[0050] 1) The treatment of the support is the same as in Example 1: the ceramic membrane is placed in deionized water for 1 hour of ultrasonic treatment, and a sheet-type alumina ceramic membrane is selected as the support. The support has a thickness of 2 mm, an outer diameter of 22 mm, and a pore size of 10 nm; then it is immersed in a 1 mol / L sodium hydroxide solution for 2 hours, taken out and dried naturally, and then placed in a 110°C oven for 6 hours. After cooling, it is immersed in a 2 mmol γ-aminopropyltrimethoxysilane ethanol solution, reacted at room temperature for 12 hours, and then rinsed with deionized water several times and dried in a 110°C oven for 6 hours.
[0051] 2) Synthesis of PIM-6: 1mmol 1,2,4,5-tetrahydroxybenzene and 1mmol tetrafluoroterephthalonitrile were added to a three-necked round-bottom flask containing 20ml N,N-dimethylformamide, and 2mmol potassium carbonate was added. The mixture was reacted at 120°C for 2 hours under a nitrogen atmosphere. After the reaction, it was washed with deionized water and methanol in turn, filtered, and dried in a vacuum oven at 110°C for 24 hours to obtain PIM-6.
[0052] 3) PIM-6 functionalization: 0.3 g PIM-6, 18 ml deionized water, 6 ml glacial acetic acid and 18 ml sulfuric acid were added to a 100 ml round-bottom flask in sequence, reacted at 150 °C for 48 hours, and after cooling, transferred to a beaker containing 500 ml deionized water. The brown powder was filtered and vacuum dried at 110 °C overnight to obtain PIM-6-COOH.
[0053] 4) Preparation of composite ceramic nanofiltration membrane is the same as in Example 1: the above-mentioned -COOH-modified PIM-6 is dissolved in chloroform at a concentration of 5 wt %. The pretreated support is immersed in the solution for 10 minutes, taken out and dried in the shade, and then placed in an oven at 80° C. for heat treatment for 12 hours. The preparation of the composite ceramic nanofiltration membrane is completed.
[0054] Membrane separation performance test: Under the test conditions of room temperature and 0.5 MPa pressure, the flux of the composite ceramic nanofiltration membrane for pure water is 31.1 LHM, and the retention rate for 0.2 wt% alkaline orange 2 (molecular weight 248 Da) aqueous solution is 95.3%.
[0055] Solvent resistance test: At 40°C, the composite ceramic nanofiltration membrane was immersed in acetone for 168 hours, and then tested at room temperature and 0.5 MPa pressure. The pure water flux was 33.6 LHM, and the retention rate of 0.2 wt% alkaline orange 2 (molecular weight 248 Da) aqueous solution was 93.3%.
[0056] Embodiment 6:
[0057] 1) The treatment of the support is the same as in Example 1: the ceramic membrane is placed in deionized water for 1 hour of ultrasonic treatment, and a sheet-type alumina ceramic membrane is selected as the support, which has a thickness of 2 mm, an outer diameter of 22 mm, and a pore size of 30 nm; then immersed in a 1 mol / L sodium hydroxide solution for 2 hours, taken out and naturally dried, and then placed in a 110°C oven for 6 hours. After cooling, it is immersed in a 2 mmol γ-aminopropyltrimethoxysilane ethanol solution, reacted at room temperature for 12 hours, and then rinsed with deionized water several times and dried in a 110°C oven for 6 hours.
[0058] 2) The synthesis of PIM-1 was the same as in Example 1: 1 mmol of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindole and 1 mmol of tetrafluoroterephthalonitrile were added to a three-necked round-bottom flask containing 20 ml of N,N-dimethylformamide, and 2 mmol of potassium carbonate was added. The mixture was reacted at 120° C. for 2 hours under a nitrogen atmosphere. After the reaction, the mixture was washed with deionized water and methanol in sequence, filtered, and dried in a vacuum oven at 110° C. for 24 hours to obtain PIM-1.
[0059] 3) PIM-1 functionalization is the same as in Example 1: PIM-1 is functionalized with ethanolamine. PIM-1 powder is placed in a three-necked flask, and an appropriate amount of ethanolamine is added. The mixture is reacted at 105°C for 12 hours under a nitrogen atmosphere. After the reaction, the mixture is poured into ethanol. After stirring for 15 minutes, the precipitate is filtered out, washed with deionized water, and dried in a vacuum oven at 110°C for 24 hours to obtain -OH-modified PIM-1 (PIM-1-OH).
[0060] 4) Preparation of composite ceramic nanofiltration membrane is the same as in Example 1: the above-mentioned -OH-modified PIM-1 is dissolved in chloroform at a concentration of 5 wt %. The pretreated support is immersed in the solution for 10 minutes, taken out and dried in the shade, and then placed in an oven at 80° C. for heat treatment for 12 hours. The preparation of the composite ceramic nanofiltration membrane is completed.
[0061] Membrane separation performance test: Under the test conditions of room temperature and 0.5 MPa pressure, the flux of the composite ceramic nanofiltration membrane for pure water is 41.4 LHM, and the retention rate for 0.2 wt% Congo red (molecular weight 696 Da) aqueous solution is 94.6%.
[0062] Solvent resistance test: The composite ceramic nanofiltration membrane was immersed in acetone for 168 hours at 40°C. Then, the pure water flux was tested at room temperature and 0.5 MPa pressure to be 33.6 LHM, and the rejection rate of 0.2 wt% Congo red (molecular weight 696 Da) aqueous solution was 92.3%.
[0063] Embodiment 7:
[0064] 1) The pretreatment of the support is the same as that in Example 1: the ceramic membrane is placed in deionized water for ultrasonic treatment for 1 hour, and a sheet-type alumina ceramic membrane is selected as the support. The support has a thickness of 2 mm, an outer diameter of 22 mm, and a pore size of 10 nm; then it is immersed in a 1 mol / L sodium hydroxide solution for 2 hours, taken out and dried naturally, and then placed in a 110°C oven for 6 hours. After cooling, it is immersed in a 2 mmol γ-aminopropyltriethoxysilane ethanol solution, reacted at room temperature for 12 hours, and then rinsed with deionized water several times and dried in a 110°C oven for 6 hours.
[0065] 2) Synthesis of PIM-1 was the same as in Example 1: 1 mmol of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindole and 1 mmol of tetrafluoroterephthalonitrile were added to a three-necked round-bottom flask containing 20 ml of N,N-dimethylformamide, and 2 mmol of potassium carbonate was added. The mixture was reacted at 120°C for 2 hours under a nitrogen atmosphere. After the reaction, the mixture was washed with deionized water and methanol in turn, filtered, and dried in a vacuum oven at 110°C for 24 hours to obtain PIM-1.
[0066] 3) Functionalization of PIM-1 was the same as in Example 1: PIM-1 was functionalized with ethanolamine. PIM-1 powder was placed in a three-necked flask, and an appropriate amount of ethanolamine was added. The mixture was reacted at 105° C. for 12 hours under a nitrogen atmosphere. After the reaction, the mixture was poured into ethanol and stirred for 15 minutes. The precipitate was filtered out, washed with deionized water, and dried in a vacuum oven at 110° C. for 24 hours to obtain -OH-modified PIM-1 (PIM-1-OH).
[0067] 4) Preparation of composite ceramic nanofiltration membrane is the same as in Example 1: the -OH-modified PIM-1 is dissolved in chloroform at a concentration of 5 wt %. The pretreated support is immersed in the solution for 10 minutes, taken out and dried in the shade, and then placed in an oven at 80° C. for heat treatment for 12 hours to complete the preparation of the composite ceramic nanofiltration membrane.
[0068] Membrane separation performance test: Under the test conditions of room temperature and 0.5 MPa pressure, the flux of the composite ceramic nanofiltration membrane for pure water is 41.4 LHM, and the retention rate for 0.2 wt% Rhodamine B (molecular weight 373 Da) aqueous solution is 95.3%.
[0069] Solvent resistance test: The composite ceramic nanofiltration membrane was immersed in acetone at 40°C for 168 hours. Then, the pure water flux was tested at room temperature and 0.5 MPa pressure to be 33.6 LHM, and the rejection rate of 0.2 wt% rhodamine B (molecular weight 373 Da) aqueous solution was 93.3%.
[0070] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a composite ceramic nanofiltration membrane, characterized in that The following steps are involved: 1) Treatment of the ceramic support: After ultrasonic treatment, the ceramic membrane support is immersed in a strong alkaline aqueous solution for activation treatment, and then placed in an oven for drying to obtain an activated ceramic membrane support; after cooling, it is immersed in an ethanol solution of a silane coupling agent, and then washed with ethanol or water, and placed in an oven for drying to obtain a grafted ceramic membrane support; 2) Functionalization of PIMs: introducing hydroxyl, amino or carboxyl active groups into the PIM chain structure through functionalization reaction; 3) Soaking the ceramic support treated in step 1) in the chloroform solution of the functionalized PIMs in step 2), taking it out after soaking, drying it in the shade, and putting it in an oven for heat treatment, so that the functional groups on the functionalized PIMs are connected to the silane coupling agent of the ceramic membrane support, thereby obtaining a composite ceramic nanofiltration membrane.
2. The method for preparing a composite ceramic nanofiltration membrane according to claim 1, characterized in that In step 1): the material of the ceramic membrane support is alumina, titanium oxide or zirconium oxide, and is in sheet, tubular or hollow fiber form, with a pore size of 10-50 nm; the strong base is at least one of sodium hydroxide, potassium hydroxide and lithium hydroxide, and the concentration of the strong base aqueous solution is 0.1-1.0 mol / L, preferably 0.2-0.8 mol / L, and more preferably 0.4-0.5 mol / L.
3. The method for preparing a composite ceramic nanofiltration membrane according to claim 1, characterized in that In step 1), the ultrasonic treatment time is 0.5-6 hours, preferably 1-5 hours, more preferably 2-3 hours; the oven drying temperature in the activation treatment is 110-180°C, and the time is 6-12 hours; preferably, the drying temperature is 140-160°C, and the time is 8-10 hours.
4. The method for preparing a composite ceramic nanofiltration membrane according to claim 1, characterized in that In step 1), the silane coupling agent is at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-diethylaminomethyltriethoxysilane and γ-diethylenetriaminopropyltrimethoxysilane; the concentration of the silane coupling agent in ethanol solution is 1-20 mmol / L, preferably 5-15 mmol / L, more preferably 8-12 mmol / L; the oven drying temperature in the grafting treatment is 110-180°C for 6-12 h; preferably the drying temperature is 150-160°C for 9-10 h.
5. The method for preparing a composite ceramic nanofiltration membrane according to claim 1, characterized in that In step 2), the PIMs is one of PIM-1-6, and the synthesis route of PIM-1-6 and the required monomer molecular structure are as follows:
6. The method for preparing a composite ceramic nanofiltration membrane according to claim 1, characterized in that In step 2), the functionalization of the PIMs is to introduce at least one of hydroxyl, amino and carboxyl groups; the mass fraction of the chloroform solution of the functionalized PIMs is 1wt%-5wt%, preferably 2wt%-3wt%.
7. The method for preparing a composite ceramic nanofiltration membrane according to claim 1, characterized in that In step 3), the oven drying temperature is 40-80°C for 6-12 hours; preferably, the drying temperature is 50-60°C for 8-10 hours.
8. The method for preparing a composite ceramic nanofiltration membrane according to claim 5, characterized in that The synthesis method of PIM-1-6 includes the synthesis of PIM-1, and the specific steps are: putting 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindole and tetrafluoroterephthalonitrile in an equal molar ratio into a three-necked flask containing N,N-dimethylformamide, adding a small amount of potassium carbonate, and reacting at 115-125° C. under vacuum conditions for 1-4 hours; after the reaction is completed, washing with deionized water and methanol in sequence, filtering and drying in a vacuum oven at 105-115° C. for 22-26 hours to obtain PIM-1.
Citation Information
Patent Citations
Synthesis of PIM (polymer of intrinsic microporosity), and preparation method and application of PIM membrane
CN107213807A
Preparation method for organic inorganic composite ceramic nanofiltration membrane
CN110038438A
Organic ceramic composite film as well as preparation method and application thereof
CN118751080A
Cited By
Composite membrane with functions of adsorption separation and catalytic degradation of new pollutants as well as preparation method and application of composite membrane
CN121911246A